SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA PENYAKIT HEWAN TERNAK RUMINANSIA BESAR - Deila Etha Pritia; Ario Yudo Husodo; Moh. Ali Albar (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2017)
Ruminant animals was a group of mammals that chew the cud or eat the food there was swallowed. In Sumbawa district, there was 10 ruminant livestock diseases that are often infected by anthrax, brucellosis, snoring or septichaemia epizootica (SE), mucus or bovine epheral fever (BEF), surra worm or thelazia, scabies and abdominal bloating. One of the obstacles in order to increase the productivity of livestock was the existence of various diseases there was any effect on the life of livestock. This system aimed to make it easier for farmers to obtained information about diseases in their animals System tested methods used to test this system was black box testing, system accuracy tested with expert, questionnaire and precision and recall accuracy tested, black box test results show all existing functions was running well. testing between the system with the expert obtained an accuracy of 93% ,. Testing questionnaire got result of conformity assessment system to user requirement or breeder with answer agreed equal to 62.68%. The testing of precision and recall obtained the result of precision testing of 95.5% and recall of 8.3%, So it can be concluded that this system was in accordance with the needs of users. Keywords: Large Ruminant, Expert System, Web, Similarity